When Crowd-Based Resources and Capabilities Generates Radical Innovation? It Depends on the Network Effects - Santoso, Adhi Setyo (International Journal of Business Studies, 2020)
Peer-to-peer or digital multi-sided platform (MSP) startups have created disruptions in various industries in the past few years. In this matter, the crowds within the platform ecosystem have significant contribution for digital MSP startups’ growth. However, there are limited studies that examine the crowd-based resource and capabilities as the source of radical innovation performance since it still conducts the perspective of linear product-market supply and demand. By using network theory, this research proposal wants to examine the role of network effects toward the development of the radical innovation. The findings of PLS-SEM analysis with 70 respondents from digital MSP startups show that crowds-based resources and capabilities manifested by integrative capabilities can generate radical innovation performance through decent network effect that enables to produce high incremental innovation performance beforehand. It shows the importance interaction between digital MSP startups with the crowds for innovation purposes. Hence, the findings contribute in open innovation literatures especially in finding the contributing factors to generate radical innovation